Challenging the Visual Discourse of Reading: or, Do Teen Readers Look Like Google Images?. Issue 2 (3rd April 2019) - Nichols, Sue; Loh, Chin Ee
ABSTRACT: Popular culture images of reading tend to portray readers as solitary individuals deeply immersed in reading a single text in a quiet, undisturbed spot. Yet, in our documentation of adolescent students reading in Singapore secondary schools, we find that there are many ways and modes of reading, much of which is social in nature. Through the use of comparative, critical visual analysis, this paper expands the understanding of what it means to read and to understand how adolescent readers experience reading in school contexts. Visual images serve to disrupt dominant readings of what counts as reading to elicit new considerations for engaging adolescents in reading.